Primary Malignancies of the Heart and Pericardium. Issue 9 (4th June 2014) - Burazor, Ivana; Aviel‐Ronen, Sarit; Imazio, Massimo; Markel, Gal; Grossman, Yoni; Yosepovich, Ady; Adler, Yehuda
ABSTRACT Primary malignancies of the heart and pericardium are rare. All the available data come from autopsy studies, case reports, and, in recent years, from large, specialized, single‐center studies. Nevertheless, if primary malignancy is present, it may have a devastating implication for patients. Malignancies may affect heart function, also causing left‐sided or right‐sided heart failure. In addition, they can be responsible for embolic events or arrhythmias. Today, with the widespread use of noninvasive imaging modalities, heart tumors become evident, even as an incidental finding. A multimodality imaging approach is usually required to establish the final diagnosis. Despite the increased awareness and improved diagnostic techniques, clinical manifestations of primary malignancy of the heart and pericardium are so variable that their occurrence may still come as a surprise during surgery or autopsy. No randomized clinical trials have been carried out to determine the optimal therapy for these primary malignancies. Surgery is performed for small tumors. Chemotherapy and radiation therapy can be of help. Partial resection of large neoplasms is performed to relieve mechanical effects, such as cardiac compression or hemodynamic obstruction. Most patients present with marginally resectable or technically nonresectable disease at the time of diagnosis. It seems that orthotopic cardiac transplantation with subsequent immunosuppressive therapy may represent an option for very carefully selected patients. Early diagnosis and radical exeresis are of great importance for long‐term survival of a primary cardiac malignancy. This can rarely be accomplished, and overall results are very disappointing.